Does seasonal variation in orthopaedic trauma volume correlate with adverse hospital events and burnout?. Issue 6 (June 2022) - Waldron, Jacob; Denisiuk, Marek; Sharma, Rajan; Boura, Judith; Afsari, Alan; Best, Benjamin
Highlights: Work relative value units are a useful and accessible metric for assessing volume in non elective orthopaedic trauma practices. We found that orthopaedic trauma volume at our level i trauma centre has a seasonal variation, with a significant increase in workload during the summer. Resident reported sleepiness on the orthopaedic trauma service was highest in the summer and correlated with seasonal variation in wRVUs. Total preventable adverse patient safety events trended higher in the summer, but were not correlated with our findings of seasonal variations in orthopaedic trauma volume. The results are applicable to various specialties involved in the care of patients with orthopaedic trauma who are interested in assessing their own practices, mitigating burnout risk and optimizing patient safety. Abstract: Introduction: Assessing workload and mitigating burnout risk should be a constant goal within training programs. By using work relative value unit (wRVU) data in a non-elective orthopaedic trauma practice, we investigated seasonal variation in workload on an orthopaedic trauma service at a level I trauma centre. We also investigated whether there was a correlation in seasonal preventable adverse patient safety events (PSEs) and resident Epworth Sleepiness Scale (ESS) scores. Materials and methods: Data on wRVUs were collected over an 8-year period for a single orthopaedic trauma surgeon with a non-elective practice. Monthly wRVU totals were tabulated over this 8-year period and compared with total hospital orthopaedic surgical trauma volume. The total number of wRVUs and surgical cases analysed were 80, 955 and 9, 928 respectively. A total of 1, 560 PSEs and four years of resident ESS scores were analysed. Data on seasonal variations was evaluated for significance utilizing the Kruskal-Wallis test. WRVUs were then compared to total case volume, PSEs, and resident ESS scores using Spearman's correlation coefficients. Results: We found that wRVUs significantly differed by month (P-value < 0.001) and season (P-value < 0.001) with the highest volume occurring in the summer months. Seasonal variation in wRVUs demonstrated a positive linear correlation with total surgical volume (P-value <0.001) and resident reported ESS scores (P-value = 0.001). PSEs were highest in the summer ( P  = 0.026), but were not correlated with our findings of seasonal variations in orthopaedic volume (P-value = 0.741). Conclusion: WRVUs of our single surgeon's orthopaedic trauma practice had a seasonal variation with significantly higher volume during the summer. These findings were representative of seasonal variations in total hospital orthopaedic trauma volume and also demonstrated correlation with objective resident sleepiness scores. PSEs were more frequent in the summer but not correlated with seasonal variation in volume. Burnout poses a risk to patient safety and has been shown to be correlated with increased work volume. These topics are important and applicable to various specialties involved in the care of patients with orthopaedic trauma injuries.